Institutional Pressures and Digital Financial Governance in Indonesian Village Governments: An Isomorphic Perspective - Syachbrani, Warka; Idrus, Mukhammad; Yusuf, Yulia Yunita; Ahmad, (Technium Social Sciences Journal, 2025)
Village governments in Indonesia are at the forefront of rural development and fiscal decentralization, making transparent and accountable financial governance essential. The recent digital transformation of public administration introduces both opportunities and challenges for villages in adopting digital financial reporting systems. Despite government mandates and standardized regulations, variations in implementation persist across regions. This study examines how institutional pressures—coercive, mimetic, and normative—isomorphism—shape the adoption of digital financial governance among 100 village governments in South Sulawesi, Indonesia. Using a mixed-method sequential explanatory approach, quantitative data were collected through surveys of village heads, treasurers, and finance staff, followed by in-depth interviews to explore contextual dynamics. Regression analysis reveals that coercive pressures from government regulations significantly influence digital adoption, while mimetic and normative pressures strengthen institutional alignment and reporting consistency. Qualitative findings show that digital systems enhance transparency but require greater training and technical support. The study contributes to institutional theory by integrating digital governance perspectives into public sector accounting at the village level. Policy implications include strengthening digital literacy among village officials, enhancing regulatory support, and promoting inter-village knowledge sharing to ensure sustainability in digital transformation.